2016
DOI: 10.1371/journal.pone.0154211
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery Restores Cardiac and Sudomotor Autonomic C-Fiber Dysfunction towards Normal in Obese Subjects with Type 2 Diabetes

Abstract: ObjectiveThe aim was to evaluate the impact of bariatric surgery on cardiac and sudomotor autonomic C-fiber function in obese subjects with and without Type 2 diabetes mellitus (T2DM), using sudorimetry and heart rate variability (HRV) analysis.MethodPatients were evaluated at baseline, 4, 12 and 24 weeks after vertical sleeve gastrectomy or Roux-en-Y gastric bypass. All subjects were assessed using SudoscanTM to measure electrochemical skin conductance (ESC) of hands and feet, time and frequency domain analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 67 publications
2
47
0
1
Order By: Relevance
“…Moreover, correlations between ESC and morphology of small fibers have been reported by some authors using skin biopsy parameters although weaker than expected and denied by others using corneal confocal microscopy measures . Finally, ESC has been advocated as a sensitive outcome in an intervention study with bariatric surgery in subjects with prediabetes and type 2 diabetes, but also the associations between ESC and CARTs were inconsistent at 1‐year follow‐up in 37 subjects with type 1 diabetes and free of complications, and the ESC decline unrelated to clinical variables and standard autonomic measures . The position statement of the American Diabetes Association did not recommend routine screening for sudomotor dysfunction in clinical practice …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, correlations between ESC and morphology of small fibers have been reported by some authors using skin biopsy parameters although weaker than expected and denied by others using corneal confocal microscopy measures . Finally, ESC has been advocated as a sensitive outcome in an intervention study with bariatric surgery in subjects with prediabetes and type 2 diabetes, but also the associations between ESC and CARTs were inconsistent at 1‐year follow‐up in 37 subjects with type 1 diabetes and free of complications, and the ESC decline unrelated to clinical variables and standard autonomic measures . The position statement of the American Diabetes Association did not recommend routine screening for sudomotor dysfunction in clinical practice …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, correlations between ESC and morphology of small fibers have been reported by some authors using skin biopsy parameters although weaker than expected 15,19,43 and denied by others using corneal confocal microscopy measures. 44 Finally, ESC has been advocated as a sensitive outcome in an intervention study with bariatric surgery in subjects with prediabetes and type 2 diabetes, 45 but also the associations between ESC and…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Casellini et al (2016) measured time and frequency domain analysis of heart rate variability before and after surgical weight loss in non-diabetic, pre-diabetic, and T2D subjects. They reported that changes in cardiac autonomic function, representing both sympathetic and parasympathetic components, were significantly greater in T2D subjects.…”
Section: Discussionmentioning
confidence: 99%
“…This concurs with the known central sympathoexcitatory effects of insulin (Anderson et al, 1991; Rahmouni et al, 2004). Other studies have shown greater improvement in glycemic and cardiac autonomic indices in T2D subjects compared to normal glucose tolerant (NGT) subjects after lifestyle induced and surgical weight loss (Solomon et al, 2010; Casellini et al, 2016). Hitherto, the relative benefits of weight loss in obese subjects with different stages of glycemic control on robust assessments of SNS activity are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis of two studies ( n= 40 participants) that examined the effect of RYGB on peripheral neuropathy in type 2 diabetes and a BMI <35 kg/m 2 reported a significant reduction in the Neuropathy Symptoms Score and Neuropathy Disability Score 12 months after surgery [effect size −3.830 (95% CI −4.234 to −3.426); P <0.001 and −2.174 (95% CI −3.093 to −1.255); P <0.0001, respectively) . A similar effect on Neuropathy Disability Score has been observed in 17 morbidly obese patients with type 2 diabetes over 24 weeks after sleeve gastrectomy and RYGB [effect size −1.188 (95% CI −1.651 to −0.726); P <0.0001] . Indeed, a recent systematic review and meta‐analysis of 420 obese participants undergoing bariatric surgery showed a significant improvement in the International Index of Erectile Function score, sexual desire, sexual intercourse satisfaction, and total satisfaction .…”
Section: Metabolic and Bariatric Surgerymentioning
confidence: 95%